Optimization of AI Utilization and Improvement of Scientific Article Writing Quality at KH. Mukhtar Syafa’at University, Blokagung, Banyuwangi - Muhammad Fauzi Al Hamidi; Nurul lailia; Hurin In Masruha; Sri Wahyuni (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2025)
This research aims to optimize the use of artificial intelligence (AI) in writing scientific articles at University of KH. Mukhtar Syafaat , an Islamic Religious University (PTKI) that is adapting to digitalization. The background of the study is low AI literacy, a gap in understanding academic ethics, and a tendency to misuse AI that threatens the integrity and originality of scientific works. The method used is Participatory Action Research (PAR), which involves lecturers and students through interviews, Focus Group Discussions (FGD), observations, and pre-post questionnaires to map practices, perceptions, and constraints. The data were analyzed with the Miles and Huberman interactive model. The results of the study show that the training and mentoring program in the Master of Service Candidate (KMM) scheme has succeeded in improving the ability of participants to systematically compile article structures, understand the role of AI as a tool, and apply ethics in the use of AI. The utilization of AI platforms such as DeepSeek, Julius, and Jeenni AI has proven to be effective in speeding up brainstorming, improving grammar, and improving writing consistency without neglecting the user's critical analysis responsibilities. Program outputs in the form of scientific articles, educational videos, and activity reports show improved quality and originality. This research produced novelty in the form of an ethical guide design that integrates technical competence, Islamic academic ethics, and the value of pesantren for the use of AI in scientific writing. These findings contribute to the development of operational standards that can be replicated in other pesantren-based universities